Anti-predator behaviour of flightless Kerguelen Pintail Anas eatoni moulting in a cave on the Kerguelen archipelago - Buffard, E (Wildfowl, 1995)
The Kerguelen Pintail is an endemic species which lives on the Crozet and Kerguelen archipelago. During the post-breeding moult, it loses its flight feathers and is unable to fly. The Kerguelen Pintail is then very vulnerable to the Brown Skua, and the ducks tend to lurk in the dense vegetation to escape predation. Where there is no tall primeval vegetation, moulting Kerguelen Pintail find protection in a cave.